Incidents in the life of a Slave girl : - Jacobs, Harriet (W.W. Norton, 2001)
Contexts includes contemporary responses to Incidents, selections from Jacobs's other published writings, and extracts from her correspondence. Criticism includes eleven important assessments of the narrative, contributed by Jean Fagan Yellin, Ann Taves, Valerie Smith, Nellie Y. McKay, Harryette Mullen, Michelle Burnham, Nell Irvin Painter, Frances Smith Foster, Sandra Gunning, Elizabeth V. Spelman, and Christine Accomando. A Chronology and Selected Bibliography are included